’I Call, You Respond?’: Game Calls, Hunting and Sound Mimicry in the Black Forest - Diane Barbé (Pulse)
This paper focuses on game calls, also known as appeaux in French or Wildlocker in German, instruments located at the intersection of interspecies communication and aesthetic creation. A reciprocal barking encounter with a roe deer in the Black Forest in Germany serves as a starting point to explore alternate semiotic registers that involve similarity and mimicry, beyond the exclusive symbolic structures of human language. This article highlights several non-symbolic properties that emerge through sound mimicry with game 1 calls: a kind of playfulness of magic, a deep emotional implication, a familiarity and embeddedness in the particular Umwelt of the individuals, and the impossibility of translation into (human) symbolic language. The article suggests that new tools for investigation need to be developed to be able to learn about these issues, as called for by recent posthuman literature on multispecies relations.